Inhibition of Breast Cancer Cell Proliferation through Disturbance of the Calcineurin/NFAT Pathway by Human Herpesvirus 6B U54 Tegument Protein - Iampietro, Mathieu (J Virol, 2014)
Nuclear factor of activated T cell (NFAT) proteins are key regulators involved in multiple physiological mechanisms, such as immune response and cell growth. The capacity of selective calcineurin/NFAT inhibitors to decrease NFAT-dependent cancer cell progression, particularly in breast cancer, has already been demonstrated. In this study, we report a role for the human herpesvirus 6B (HHV-6B) U54 tegument protein in inhibiting MCF-7 breast cancer cell proliferation by inhibiting NFAT activation.